Dynamic Searchable Symmetric Encryption Technique for Secure Cloud Storage - Mallem Anusha; DR. K. Venkataramana (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Dynamic Searchable Symmetric Encryption (DSSE) plays a crucial role in enabling secure keyword searches over encrypted data stored in the cloud. It allows users to outsource search functionality to cloud servers without exposing the underlying data. While many existing DSSE approaches emphasize strong security features such as forward security and Type-I-backward security to prevent data leakage, they often neglect resilience against unintended or faulty client actions—like repeated operations or attempts to delete entries that don’t exist—which can lead to inaccurate search results. To overcome these limitations, this paper introduces two enhanced DSSE models, named SR-DSSE a and SR-DSSE b. These schemes not only uphold forward and Type-I-backward security but also focus on improving robustness to ensure accurate search outcomes even when clients make errors. Leveraging AES encryption, the proposed methods are particularly suitable for securing sensitive data, such as medical records, and are demonstrated in healthcare environments involving interactions among patients, doctors, cloud providers, and trusted entities.
Keywords: DSSE; Doctor; Patient; Cloud Server; Trusted Authority; AES; Encryption; Decryption